International Community Service for Strengthening Students’ Motivation and Islamic Educational Values at Dayah Darul Hikmah, Aceh Besar - Hendra Halim; Muhammad Haris Riyaldi; Md Yazid Ahmad; Noor Lizza Mohamed Said; Nurul Ilyana Muhd Adnan; Ahmad Nizam; Khairil Umuri (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2026)
This community service activity strengthened students’ learning motivation, self-confidence, Islamic knowledge awareness, and initial understanding of sharia-based economic self-reliance at Dayah Darul Hikmah, Aceh Besar. It was implemented through international collaboration among the Islamic Economics Study Program, Faculty of Economics and Business, Universitas Syiah Kuala, the Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, and Dayah Darul Hikmah. The activity aimed to provide educational, motivational, and social support while introducing professional governance and economic independence for Islamic boarding schools. An educative, participatory, interactive, and collaborative method was applied through coordination, opening ceremony, motivational sessions, Islamic knowledge reinforcement, discussion, question-and-answer session, social assistance distribution, documentation, and evaluation. The strategies included inspirational lectures, direct interaction, reward-based participation, institutional collaboration, and social care. The results showed active student participation, strong enthusiasm, direct educational and social benefits, and strengthened international partnerships supporting SDGs related to quality education, reduced inequalities, decent work, and partnerships for development.